Synthesis and structure of 3,4-dihydropyrido[2’,3’:3,4]pyrazolo[1,5-a][1,3,5]triazin-2-amines - Dolzhenko, Anton; Bai, S.; Dolzhenko, A.; Chui, W. (John Wiley & Sons, 2012)
A new convenient synthon for heterocyclic chemistry, namely 1H-pyrazolo[3,4-b]pyridin-3-ylguanidine was successfully prepared by selective guanylation of 1H-pyrazolo[3,4-b]pyridin-3-amine. A series of 3,4-dihydropyrido[2′,3′:3,4]pyrazolo[1,5-a][1,3,5]triazin-2-amines was synthesized from 1H-pyrazolo[3,4-b]pyridin-3-ylguanidine using aldehydes or ketones as one-carbon inserting reagents. The tautomeric preferences of the products were determined using spectroscopic (e.g., 2D NOESY NMR) and single crystal X-ray diffraction data.